Legal learning and saintly authority in thirteenth-century hagiography: the Magna vita sancti Hugonis. Issue 1 (1st January 2018) - Byrne, Philippa
ABSTRACT: Law is central to the construction of sanctity in Adam of Eynsham's Magna vita of Hugh of Lincoln (1186–1200). Hugh had no formal training in canon law, and, beyond the Magna vita, there is no evidence to suggest that he was a particularly proficient judge. If that lack of legal training was not a problem in Hugh's lifetime, it had become a more sensitive issue by c .1212, the date of the composition of the Magna vita . Rather than ignoring the law, or denying its importance, Adam attempted to demonstrate that Hugh received mastery of legal argument as a divine gift, and multiple miracles involve Hugh correcting legal scholars. Recognising these careful patterns of construction raises problems for reading Adam's Magna vita . While Adam has traditionally been characterised as a truthful biographer, this reading suggests he was engaged in a more complex project of marrying sanctity to legal learning.